251 Knowledge of the importance of proper tackle contact techniques does not translate to proper tackle contact technique for injury prevention and performance. (3rd March 2020) - Hollander, Steve den; Lambert, Mike; Jones, Ben; Hendricks, Sharief
Abstract : Background: In rugby union and sevens, the tackle is the most frequently occurring contact event and carries the greatest risk of causing injury. Proper tackle technique has been shown to reduce the risk of injury during the tackle and increase likelihood of success. As such, national rugby injury prevention programmes aim to provide coaches, trainers and players with knowledge of proper tackle technique. This knowledge is intended to modify players behaviours towards safety in the tackle, and ultimately improve their tackle technique in training and matches. Objectives: To determine the association between knowledge of the importance of proper tackle contact techniques and actual proper tackle contact technique for injury prevention and performance. Design: Cross-sectional study design. Participants: Fifty-three (n=53) academy rugby players participated in this study, and a total of 211 tackles were analysed. Assessment of risk factors: Knowledge and attitudes of proper contact technique for injury prevention and performance for both the ball-carrier and tackler were determined using a questionnaire. In training, players performed four ball-carries into contact and four tackles using a validated tackle drill. Thereafter, technical proficiency for the ball-carrier and tackler were scored using a standardised technical criteria. Main outcome measurements: Knowledge and attitude score for proper tackle contact technique for injury prevention and performance, technical proficiency score for the ball-carrier and tackler. Results: No association was found between player knowledge of the importance of techniques and actual tackle contact technique in training for both injury prevention (tackler r=-0.02, p=0.90; ball-carrier r=-0.26, p=0.06) and performance (tackler r=0.02, p=0.86; ball-carrier r=-0.13, p=0.38). Conclusions: This study reveals the gap between players' declarative knowledge of safe and effective techniques and their procedural knowledge of how to execute proper techniques. This gap supports the argument that injury prevention programmes should not be limited to educational strategies only, and should include practical coaching components.